Molecular characterization of the ITS-2 fragment of Paramphistomum leydeni (Trematoda: Paramphistomidae) - Sanabria, Rodrigo Eduardo Fabrizio (2011)
Paramphistomosis has shown an increased spread over the last years in Argentina, being in some regions an emerging parasitosis, which has motivated their study and identification. Even when morphological features were reported, molecular characterization appears as a complementary and reliable tool. Samples of Paramphistomum leydeni collected since 2002 from different origin, definitive hosts, natural or experimental infections and preservation method were subjected to PCR-RFLP for ITS2+ fragment, and compared to Fasciola hepatica and Notocotilidae cercarie. Frozen and ethanol fixed samples amplified fragments of 500 bp for P. leydeni and Notocotilidae samples, while F. hepatica eggs produced a 540 bp amplicon. Restriction fragments obtained from endonucleases HinfI, HhaI, BsuRI, TaqI, and TruI were identical for all P. leydeni samples, supporting the morphological classification previously performed. Four selected amplicons were sequenced and reported at GenBank, given a consensus sequence ITS-2+ of 441 bp. This first report of molecular characterization for P. leydeni, improves the current knowledge of the genus and establishes precedents for further specimen classifications.